Experimental Assessment on the Hysteretic Behavior of a Full-Scale Traditional Chinese Timber Structure Using a Synchronous Loading Technique - XiWang Shi; Y. Frank Chen; JinYong Chen; QingShan Yang; TieYing Li (Advances in Materials Science and Engineering)
In traditional Chinese timber structures, few tie beams were used between columns, and the column base was placed directly on a stone base. In order to study the hysteretic behavior of such structures, a full-scale model was established. The model size was determined according to the requirements of an eighth grade material system specified in the architectural treatise Ying-zao-fa-shi written during the Song Dynasty. In light of the vertical lift and drop of the test model during horizontal reciprocating motions, the horizontal low-cycle reciprocating loading experiments were conducted using a synchronous loading technique. By analyzing the load-displacement hysteresis curves, envelope curves, deformation capacity, energy dissipation, and change in stiffness under different vertical loads, it is found that the timber frame exhibits obvious signs of self-restoring and favorable plastic deformation capacity. As the horizontal displacement increases, the equivalent viscous damping coefficient generally declines first and then increases. At the same time, the stiffness degrades rapidly first and then decreases slowly. Increasing vertical loading will improve the deformation, energy-dissipation capacity, and stiffness of the timber frame.